An assessment of land deals undertaken by the National Oil Palm Project in Kalangala and Buvuma districts - Kakungula-Mayambala, R.; Tibugwisa, D.N. (Ecological Trends Alliance, 2019)
Land as a key resource requires utmost attention to avert conflicts, especially with large agrarian projects like oil palm development. Gaps in implementing policy and Free Prior Informed Consent (FPIC) in the oil palm establishment and expansion are resulting in unprecedented land issues.